Anomalous dispersion X-ray diffraction study of Pb/Bi ordering/disordering states in PbTiO3-based perovskite oxides. Issue 3 (19th December 2016) - Lin, Kun; Wang, Na; You, Li; Li, Qiang; Kato, Kenichi; Chen, Jun; Deng, Jinxia; Xing, Xianran
Abstract : We give strong evidence that Pb 2+ /Bi 3+ tend to be disordered in perovskite structures, which is attributed to similar electron configurations and comparable coordinate environments. Abstract : Synchrotron radiation-based anomalous dispersion X-ray powder diffraction (ADSPD) was carried out to reveal the Pb/Bi ordering/disordering states in a series of PbTiO3 -based negative thermal expansion materials (1 − x )PbTiO3 − x BiFeO3 ( x = 0.1, 0.3, 0.5) and (1 − x )PbTiO3 − x Bi(Zn1/2 Ti1/2 )O3 ( x = 0.1, 0.2, 0.3). It gives strong evidence of the disordered Pb/Bi distributions in these compositions, which is consistent with electron diffraction studies. Combined with binding energy calculation, we show that the disordered nature of Pb/Bi distributions is likely to be attributed to the similar electron configurations of Pb 2+ and Bi 3+ as well as their comparable coordinate environments in perovskite structures. The results of this study may be helpful to better understand the structure–property relationship in Pb/Bi-containing perovskites and are useful for further developing underlying physics in relevant materials.